Soil erosion hazard assessments in the Fraser’s Hill and the Genting Highlands using "ROM" scale / Zulkifli Abu Hassan - Abu Hassan, Zulkifli (2005)
Rainfall-induced landslides have caused severe environmental, engineering and socio-economic repercussions in Malaysia. Highland areas in this country, which are perennially very wet such as in the Fraser's Hill and the Genting Highlands receive annual rainfall in excess of2, 000 mm. With steep natural and cut-slopes topography, it has made these areas prone to erosion or landslide to occur. A study was initiated to classify the areas and predict potential erosion or landslide locations of occurrence in both the Fraser's Hill and the Genting Highlands. The classification was done by determining the soil susceptibility for failure in terms of its soil erodibility index value with regard to the "ROM" Scale. Soil samples were taken on the slopes at every 1 km stretch along the main road leading to both highlands. The erodibility index value obtained from the samples was used to grade and rank the slopes along both roads. Concurrently, daily rainfall data of both areas were thoroughly examined to determine the erosion risk frequency. From the analysis of soil samples, Km 13-14 in the Genting Highlands had been identified as the most susceptible location with erodibility index value of 4.35, which is classified as High on the "ROM" Scale. While in the Fraser's Hill, Km 4-5 tops the ranking, recording an erosion index value of 5.37 which is also high in classification. The analyzed rainfall data however, had shown that the erosion frequency is at the highest risk in the month of November and September for both the Genting Highlands and the Fraser's Hill respectively. The results also highlighted and identified the erosion hazards locations and the time of possible impact risk. With implications for combining these results with the GIS and other thematic map data, the findings would greatly facilitate future assessment and estimation of erosion hazards in both areas.